Law and sustainability: Perspectives for Lithuania and Beyond (Wydawnictwo Księgarnia Akademicka, 2023)
Law fostering sustainability and sustainable development is one of the fastest-developing, most challenging legal disciplines globally. Sustainability has many different definitions, but its essence was articulated by the Brundtland Commission, tasked by the UN in 1987 to formulate a global agenda for change: “Sustainable development is development that meets the needs of the present without compromising the ability of future generations to meet their own needs.” The edited volume Law and Sustainability analyses the ways on how law and legal profession should change and contribute to sustainability.